Tick-borne haemoparasite occurrence and Anaplasma bovis strain diversity in eastern rock sengis (Elephantulus myurus) - Oosthuizen, Marinda C. (University of Pretoria, 2026)
Dissertation (MSc)--University of Pretoria, 2018.